Italy on COVID-19: Response and Strategy - Fadhila Inas Pratiwi; Lilik Salamah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2020)
Coronavirus Diseases (COVID-19) in Italy was remarkably immense, with more than two hundred thousand infected cases, and more than thirty thousand people had died because of the virus as of 27th July 2020. The high number of mortality rate makes the Italy case is essential to be further explored. This article aims to elaborate on government response and strategy in handling COVID-19 that spread within the country. This article unfolds in four sections; the first part discusses how COVID-19 could spread massively in Italy and cause death for a thousand people. The second part explains the government measure and its effectivity in containing the virus. The third part elaborates on the impact of COVID-19 along with the government response in the socio-economic aspect. The last part explores the future of Italy after COVID-19. The article employs a literature review that analyzes information from various sources such as academic journals, research reports from the think tank, and news media outlets. Keywords: Coronavirus, Italy, Government, Response Kasus coronavirus di Italia sangat tinggi dan massif dengan lebih dari dua ratus ribu orang terinfeksi dan lebih dari lima puluh ribu orang meninggal pertanggal 27 Juli 2020. Tingginya jumlah orang yang terinfeksi dan jumlah orang yang meninggal membuat Italia menjadi kasus yang menarik untuk dibahas. Tujuan dari artikel ini untuk mengelaborasi tentang bagaimana respon dan strategi pemerintah Italia dalam menangani virus yang sudah menyebar di Italia. Artikel ini terdiri dari empat bahasan, pertama membahas tentang awal mula COVID-19 bisa menyebar secara masif di Italia dan mengakibatkan puluhan ribu orang meninggal. Kedua, membahas tentang bagaimana respon dari pemerintah Italia dan juga efektifitasnya dalam menangani penyebaran virus ini. Ketiga, membahas tentang dampak yang diakibatkan dari COVID-19 beserta respon pemerintah terhadap aspek sosio-ekonomi di Italia. Keempat, mendiskusikan bagaimana masa depan Italia setelah COVID-19. Artikel ini menggunakan tinjauan pustaka untuk melakukan analisis terkait dengan topik artikel yang berasal dari banyak sumber seperti jurnal akademis, laporan peneltian, artikel berita dan lain sebagainya. Kata-kata Kunci: Coronavirus, Italia, Pemerintah, Respons